Evacuation Preparedness in the Event of Fire in Intensive Care Units in Sweden: More is Needed. Issue 3 (10th March 2017) - Löfqvist, Erika; Oskarsson, Åsa; Brändström, Helge; Vuorio, Alpo; Haney, Michael
Abstract: Introduction: Hospitals, including intensive care units (ICUs), can be subject to threat from fire and require urgent evacuation. Hypothesis: The hypothesis was that the current preparedness for ICU evacuation for fire in the national public hospital system in a wealthy country was very good, using Sweden as model. Methods: An already validated questionnaire for this purpose was adapted to national/local circumstances and translated into Swedish. It aimed to elicit information concerning fire response planning, personnel education, training, and exercises. Questionnaire results (yes/no answers) were collected and answers collated to assess grouped responses. Frequencies of responses were determined. Results: While a written hospital plan for fire response and evacuation was noted by all responders, personnel familiarity with the plan was less frequent. Deficiencies were reported concerning all categories: lack of written fire response plan for ICU, lack of personnel education in this, and lack of practical exercises to practice urgent evacuation in the event of fire. Conclusions: These findings were interpreted as an indication of risk for worse consequences for patients in the event of fire and ICU evacuation among the hospitals in the country that was assessed, despite clear regulations and requirements for these. The exact reasons for this lack of compliance with existing laws was not clear, though there are many possible explanations. To remedy this, more attention is needed concerning recognizing risk related to lack of preparedness. Where there exists a goal of high-quality work in the ICU, this should include general leadership and medical staff preparedness in the event of urgent ICU evacuation. E Löfqvist, A Oskarsson, H Brändström, A Vuorio, M Haney .Evacuation preparedness in the event of fire in intensive care units in Sweden: more is needed .Prehosp Disaster Med .2017 ;32 (3 ):317 –320 .